PENGGUNAAN MEDIA KONKRET DALAM PEMBELAJARAN PECAHAN DI SEKOLAH DASAR - Ifadatul Mgfiroh; Zakiyah Jihan Aurelia; Muhammad Zidan Fakhruddin; Dian Mustika Anggraini (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study aims to explore elementary school teachers' perspectives on the use of concrete media in fraction learning, particularly in grade 3. The research employs a qualitative approach with in-depth interview method conducted with a teacher at SDN 2 Getas Pejaten. The findings reveal that concrete media, such as ice cream sticks used as tally marks (turus), significantly enhance student creativity and motivation. Students showed high enthusiasm and engagement when using hands-on materials. The teacher noted that concrete media is aligned with lesson plans (RPP) and positively impacts student comprehension and learning outcomes. Main challenges include varying student abilities in manipulating the media. The teacher hopes for additional visual media, such as Smart TV, to complement concrete tools. This study suggests that concrete media remains a primary and effective instructional tool for elementary mathematics, particularly for fraction concepts.